STRATEGI MITIGASI RISIKO KEUANGAN DALAM MENINGKATKAN STABILITAS PERUSAHAAN DI ERA DIGITAL (PT. UNILEVER INDONESIA Tbk.) - Supratno, Setyo; Holiawati, Holiawati (Komunitas Manajemen Kompetitif, 2025)
The rapid development of digital technology has had a significant impact on global business dynamics, including the financial stability of companies. This study aims to analyze the effectiveness of financial risk mitigation strategies in enhancing the financial stability of PT Unilever Indonesia Tbk amidst the challenges of the digital era. The method used is a descriptive quantitative approach with secondary data analysis sourced from the company’s financial statements for the period 2022 to 2024. The financial stability indicators analyzed include Debt to Equity Ratio (DER), Current Ratio (CR), and Return on Assets (ROA). The results show that the risk mitigation strategies implemented by the company have produced mixed outcomes. In 2023, the company managed to curb the increase in liabilities. However, in 2024, reliance on debt rose sharply, as reflected in the DER which increased to 6.47. In terms of liquidity, the decline in the CR to 0.45 indicates that the cash and current asset management strategies were not optimal. Additionally, the decrease in ROA to 20.9% reflects reduced efficiency in utilizing assets to generate profits. These findings are consistent with financial risk management theory, which states that excessive reliance on debt increases solvency and liquidity risks.This study recommends that the company undertake funding restructuring, strengthen cash management, expand income diversification, enhance risk protection through hedging, and maximize digital investment not only for efficiency but also for innovation and growth. Keywords: Financial risk, financial stability, Debt to Equity Ratio (DER), Current Ratio (CR), Return on Assets (ROA), mitigation strategy, digital era.